Using a Mobile Application to Teach Mathematics to Learners with Special Educational Needs: Exploring Teachers’ Experiences: Exploring Teachers’ Experiences - Mboneni, Zandile; Cronje, Johannes (Journal of Education Technology, 2024)
Mathematics apps are increasingly being used to help learners improve their mathematics skills. The debate on their effectiveness suggests that they offer learners a personalized learning experience and the flexibility to learn anywhere and anytime. However, previous evaluation literature has demonstrated the effectiveness of mobile apps from learners’ perspectives. However, it offers little insight into how teachers view the use of mathematics apps to support learners with special educational needs, particularly in developing countries. This study aimed to analyze the experiences of secondary school teachers using the Siyavula app to improve the mathematics skills of learners with special educational needs. The study used a qualitative case study methodology. The sample included two female and two male teachers, with two male participants having more than 25 years of teaching experience. The data collection method used semi-structured interviews. The data collection instrument used a questionnaire. The data analysis technique used qualitative descriptive analysis. The study results showed that teachers faced more challenges than benefits when using Siyavula, including technical issues, overwhelming content, and limited adaptability to varying learner needs. Despite these challenges, teachers recognized the potential of Siyavula, particularly its detailed progress-tracking capabilities. This study provides valuable insights into the complex dynamics of integrating technology into mathematics education for learners with special educational needs.